Cloud native network for intelligent Internet of everything - Quan YU; Dandan LIANG; Wei ZHANG (物联网学报)
A new cloud native network architecture for the future network architecture design in the era of intelligent Internet of everything was proposed, that is, network of the cloud, for the cloud, and by the cloud.Furthermore, the concept and mechanism of Cybertwin were proposed to tackle the challenges of mobility, security and availability in cloud native network.Three fundamental questions of cloud native network architecture design were also elaborated, that is, addressing, indexing and resource orchestration.Finally, 6G use cases and future research topics of Cybertwin based cloud native network were discussed.